2014
DOI: 10.1016/j.neulet.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Intra-nucleus accumbens administration of the calcium/calmodulin-dependent protein kinase II inhibitor KN93 induced antinociception in rats with mononeuropathy

Abstract: The present study was conducted on rats with mononeuropathy induced by left common sciatic nerve ligation. Unilateral sciatic nerve loose ligation produced decreases of the hindpaw withdrawal latency (HWL) to noxious thermal and mechanical stimulation. Intra-nucleus accumbens (NAc) injection of 1μg, 3μg and 6μg of KN93, the calcium/calmodulin-dependent protein kinase II (CaMKII) inhibitor, dose-dependently increased the HWL in mononeuropathic rats. Furthermore, intra-NAc administration of morphine, the HWL to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The response to pain of the normal side after mononeuropathy was similar to normal rats as suggested by our results (Fig. 2), thus it is reasonable that the normal side is less sensitive to drug treatments, consistent with our previous study [17] .…”
Section: Resultssupporting
confidence: 92%
“…The response to pain of the normal side after mononeuropathy was similar to normal rats as suggested by our results (Fig. 2), thus it is reasonable that the normal side is less sensitive to drug treatments, consistent with our previous study [17] .…”
Section: Resultssupporting
confidence: 92%
“…Recent pain studies have shown that the NAc also plays a major role in pain modulation and antinociceptive tolerance and acts as a source of analgesia [ 1 , 15 , 16 ]. The authors’ earlier report showed that the microinjection of the CaMK II inhibitor autocamtide-2-related inhibitory peptide (AIP) or KN93 into the NAc alleviates pain that is related to behaviors in the peripheral neuropathic pain model [ 17 , 18 ]. However, the role of CaMK II in the NAc in naïve and morphine-tolerant rats has yet to be the subject of in-depth examination.…”
Section: Introductionmentioning
confidence: 99%